Iterative method for solving the second boundary value problem (BVP) for Biharmonic type equation - Á, Đặng Quang (Journal of Computer Science and Cybernetics, 2016)
Solving BVPs for the fourth order differential equations by the reduction of them to BVPs for the  second order equations with the aim to use the achievements for the latter ones attracts attention from many researchers. In this paper, using the technique developed by  ourselves in recent works, we construct iterative method for the second BVP for  biharmonic type equation. The convergence rate of  the method is established.